Evaluation of the anticorrosion performance of peel garlic extract as corrosion inhibitor for ASTM 1020 carbon steel in acidic solution - Barreto,Lhaira Souza (2017)
ABSTRACT Metallic corrosion can be delayed using corrosion inhibitors. However, several industrial corrosion inhibitors are toxic and harmful to the environment and to the human health. In this context, in the last decades, research has been developed to investigate the performance of low toxicity corrosion inhibitors as green inhibitors obtained from vegetables, which are environmentally acceptable. The present work studied the corrosion inhibition efficiency of peel garlic extract (Allium sativum. L.) for possible replacement of benzotriazole (BTAH) on the corrosion inhibition of ASTM 1020 carbon steel (CS-1020) in 0.5 mol. L−1 hydrochloric acid media. Weight loss measurements, anodic and cathodic potentiodynamic curves and electrochemical impedance (EIS) experiments were carried out. The Fourier transformed infrared spectroscopy (FTIR) was carried out to evaluate the chemical compounds. The morphological characterization was obtained to observe the inhibitor effect in the corrosion products on substrate surface. The results showed that the addition of both inhibitors effectively hinder the corrosion process and indicated their adsorption on the electrode surface. The inhibiting efficiency of the peel garlic extract was only slightly inferior to BTAH showing that the former inhibitor can be an environmentally friendly option to toxic inhibitors. The FTIR analysis showed the presence of chemical compounds which presents antioxidant properties.